2009
DOI: 10.1186/1743-422x-6-126
|View full text |Cite
|
Sign up to set email alerts
|

Partial direct contact transmission in ferrets of a mallard H7N3 influenza virus with typical avian-like receptor specificity

Abstract: Background: Avian influenza viruses of the H7 subtype have caused multiple outbreaks in domestic poultry and represent a significant threat to public health due to their propensity to occasionally transmit directly from birds to humans. In order to better understand the cross species transmission potential of H7 viruses in nature, we performed biological and molecular characterizations of an H7N3 virus isolated from mallards in Canada in 2001.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 34 publications
2
25
0
Order By: Relevance
“…This is consistent with previous reports on limited seroconversion against H7 and H5 viruses (30,31). Collectively, the results of the WT H7N1 transmission study suggest that the virus has a limited ability to be transmitted to CH ferrets and is not capable of airborne transmission, consistent with similar studies of H7N3 viruses (5,26). A prominent feature of this experiment was the finding that two DI animals and one CH ferret developed neurological disease.…”
Section: Serial Passage Of H7n1 Yields a Virus Capable Of Airborne Trsupporting
confidence: 81%
See 1 more Smart Citation
“…This is consistent with previous reports on limited seroconversion against H7 and H5 viruses (30,31). Collectively, the results of the WT H7N1 transmission study suggest that the virus has a limited ability to be transmitted to CH ferrets and is not capable of airborne transmission, consistent with similar studies of H7N3 viruses (5,26). A prominent feature of this experiment was the finding that two DI animals and one CH ferret developed neurological disease.…”
Section: Serial Passage Of H7n1 Yields a Virus Capable Of Airborne Trsupporting
confidence: 81%
“…All ferret studies were performed with approval from the UMD Institutional Animal Care and Use Committee (protocols R-09-93 and R-12-101) and were performed under BSL3ϩ conditions in HEPA-filtered poultry isolators as previously described (25)(26)(27)(28). BSL3ϩ animal rooms are equipped with motion sensor digital video cameras in order to monitor animal behavior, as well as entry and exit of personnel.…”
Section: Methodsmentioning
confidence: 99%
“…Increased receptor binding for ␣2,6-linked sialic acid, conferred either by mutations in the receptor-binding domain, as seen in H7N9 LPAI virus, or by a deletion in the HA loop, as observed in A/New York/107 (H7N2) virus, has been associated with enhanced transmissibility for some H7 viruses, as has heightened viral replication conferred by the PB2-E627K mutation (14,16,34,35). However, other viruses, such as A/Mallard/Alberta/24/01 (H7N3) virus, which possess typical ␣2,3-linked sialic acid binding and have no known mammalian adaption mutations, still exhibit partial to full transmission among ferrets in direct contact (21,36), suggesting that other molecular determinants associated with H7 virus transmission remain unidentified.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that both LPAI and HPAI H7N3 viruses are capable of efficient replication throughout the respiratory tract of ferrets; however, H7N9 viruses have not been examined in this model (10,14,15,34). Ferrets were inoculated i.n.…”
Section: Pathogenicity Of H7n3 and H7n9 Influenza A Viruses Followingmentioning
confidence: 99%
“…However, several North American low-pathogenicity avian influenza (LPAI) H7N2 and HPAI H7N3 viruses are highly infectious in mice and capable of limited transmission among ferrets in direct contact (11,14,15). Unlike other virus subtypes, H7 influenza viruses of both lineages have predominantly been associated with ocular disease, typically, conjunctivitis, in humans (1,3,7).…”
mentioning
confidence: 99%